Commenting a heroicomic poem (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
No longer commented on for more than half a century, the Tassoni’s Secchia rapita needs a modern interpretation that makes use of the results of research carried out in recent years and offers a new perspective on reading the text. The paper questions the additional problems with respect to the normal commentary that a heroicomic text presents to those who wish to interpret it.
Keywords: Alessandro Tassoni; commentary; Secchia rapita; heroicomic